2013
DOI: 10.1186/1471-2229-13-6
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of microRNA171 affects phase transitions and floral meristem determinancy in barley

Abstract: BackgroundThe transitions from juvenile to adult and adult to reproductive phases of growth are important stages in the life cycle of plants. The regulators of these transitions include miRNAs, in particular miR156 and miR172 which are part of a regulatory module conserved across the angiosperms. In Arabidopsis miR171 represses differentiation of axillary meristems by repressing expression of SCARECROW-LIKE(SCL) transcription factors, however the role of miR171 has not been examined in other plants.ResultsTo i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(96 citation statements)
references
References 47 publications
7
76
0
1
Order By: Relevance
“…Notably miR171a* is also functional in gene silencing and the miR171a*- SU(VAR)3-9 HOMOLOG8 pair was proposed to have evolved very recently in the Arabidopsis lineage [44]. A recent report showed that overexpression of miR171 ( Hvu-pri-miR171a ) in barley up-regulated miR156 and repressed vegetative phase transitions [49], which is in contrast with the opposite effects of the two miRNAs in Arabidopsis described herein and reported by others [26], [29], [50]. Whether the interplay between the two conserved aging miRNAs varies with plant taxa is a subject of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Notably miR171a* is also functional in gene silencing and the miR171a*- SU(VAR)3-9 HOMOLOG8 pair was proposed to have evolved very recently in the Arabidopsis lineage [44]. A recent report showed that overexpression of miR171 ( Hvu-pri-miR171a ) in barley up-regulated miR156 and repressed vegetative phase transitions [49], which is in contrast with the opposite effects of the two miRNAs in Arabidopsis described herein and reported by others [26], [29], [50]. Whether the interplay between the two conserved aging miRNAs varies with plant taxa is a subject of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis plants overexpressing miR168a display abscisic acid hypersensitivity and drought tolerance (Li et al 2012). The overexpression of miR172 promotes leaf length elongation in adult plants and increases root and hypocotyl growth (Kim et al 2014), and miR171 overexpression affects floral meristem determinancy in barley (Curaba et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Barley plants overexpressing miR171 were dwarf and had a reduced number of tillers compared with WT, whereas rice miR171 overexpression lines were taller and had increased tiller numbers compared with WT (45,46). In Arabidopsis, miR171 targets the scarecrow-like (SCL) transcription factors and is thought to regulate meristematic cell proliferation, polar organization, and chlorophyll synthesis (47,48).…”
Section: Identification Of Multiple Rice Mirnas With Effects On Agronmentioning
confidence: 99%